Aspetti biologici e socio-culturali dell’emozione scenica: L’impostazione metodologica di L. S. Vygotskij - Carlotti, Edoardo Giovanni (Mimesis Journal, 2015)
Vygotskij’s interest in the arts, and the psychological basis of human response to artworks, was attested by his posthumous book bearing the title of Psychology of Art. There, theatrical problems were barely touched on, and dramatic writing came to the fore. Though, the Soviet psychologist took care to point out that “fifty percent” only of a play can be revealed by its written form, and an extensive research on acting and stage expression was needed to fully understand dramatic meanings. On the Problem of the Psychology of the Actor’s Creative Work briefly summarizes Vygotskij’s concept of the actor’s experience and expression as a peculiar condition of human mental life, whose survey may shed light upon wider questions concerning emotional processes and their connection with the mind-body problem. However, such questions cannot be approached by starting from an exclusive standpoint, be it either naturalistic or cultural, but a methodological attitude is needed that can assimilate – and complement each other – the results of biological, historical and social studies.